2013
DOI: 10.1387/ijdb.130047av
|View full text |Cite
|
Sign up to set email alerts
|

Role of cyclins in controlling progression of mammalian spermatogenesis

Abstract: Cyclins are key regulators of the mammalian cell cycle, functioning primarily in concert with their catalytic partners, the cyclin-dependent kinases (Cdks). While their function during mitosis in somatic cells has been extensively documented, their function during both mitosis and meiosis in the germ line is poorly understood. From the perspective of cell cycle regulation there are several aspects of mammalian spermatogenesis that suggest unique modes of regulation and hence, possible unique functions for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 81 publications
(98 reference statements)
0
49
0
1
Order By: Relevance
“…The G 1 /S checkpoint is essential to ensure that all conditions of cell division are successfully met and to guarantee the possibility of replicating the DNA and producing healthy daughter cells. This transition is signalled and controlled by cyclins and cyclin-dependent kinases (CDKs) (Neganova and Lako 2008;Wolgemuth et al 2013). Cyclins are the principal cell cycle regulatory proteins, and have been identified in simple as well as higher-order organisms (Wolgemuth et al 2002).…”
Section: Biological Functions and Canonical And Metabolic Pathways Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The G 1 /S checkpoint is essential to ensure that all conditions of cell division are successfully met and to guarantee the possibility of replicating the DNA and producing healthy daughter cells. This transition is signalled and controlled by cyclins and cyclin-dependent kinases (CDKs) (Neganova and Lako 2008;Wolgemuth et al 2013). Cyclins are the principal cell cycle regulatory proteins, and have been identified in simple as well as higher-order organisms (Wolgemuth et al 2002).…”
Section: Biological Functions and Canonical And Metabolic Pathways Ofmentioning
confidence: 99%
“…Although the function of cyclins during mitosis and meiosis has been studied in somatic cells, their function during mitosis and meiosis in the germ line is poorly understood. Wolgemuth et al (2013) reported that cyclin A2 is highly expressed in differentiated Type A and B spermatogonia and plays an important role during both meiosis and mitosis in the germ cell line. Based on the IPA in the present study, G 1 /S checkpoint regulation and cyclin and cell cycle regulation are the most highly significantly enriched canonical pathway identified for the DE genes.…”
Section: Biological Functions and Canonical And Metabolic Pathways Ofmentioning
confidence: 99%
“…To date, regulation of the cell cycle in human spermatogonia is poorly understood (47). A disruption of the Drosophila DDX3Y homologue Belle leads to severe germ cell loss through apoptosis in the testes, while somatic cyst cells are retained intact (34).…”
Section: Discussionmentioning
confidence: 99%
“…The second meiotic division occurs in secondary spermatocytes and results in the formation of round haploid spermatids. The molecular mechanisms of chromosome pairing, meiotic recombination, chromatin modifications, and cell cycle control during meiotic division in spermatogenesis are outside the scope of this review but have been recently reviewed by others (57)(58)(59).…”
Section: Meiotic Entry In Mature Testesmentioning
confidence: 99%